A simple method to estimate seismic subsidence in soft soil under amplitude non-stationary seismic action - Gan-Ling Xian; Jing-Yan Lan; Li-Chun Chen; Yong-Zhi Wang; Lei Wang; Zhao-Ran Wu (Engineering Geology, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Seismic data processing key technology for coalbed methane reservoir - Ming Zhang; Bao-yin Zhao; Zhi-fang Ran; Wen-wu Shi; Hao Li; Kai-long Wu; Gen-yang Tang (Applied Geophysics, 2026)

Zero-valent iron induced redox oscillations: Mechanisms of dynamic Fe(II) promote ferrihydrite transformation and lattice immobilization for Pb, Cd, and As - Zhi Jiang; HongZhen Ran; Lin Yu; PengWei Zhao; Weichun Yang (Chemical Engineering Journal, 2026)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Development of a Probe-Based quantitative PCR assay for detecting Nosema bombycis and its application in inspection and quarantine of silkworm egg production - Zhangshuai He; Fangli Xie; Zhuoxi Fan; Yufan Jian; Maoshuang Ran; Yixiang Yu; Ruoheng Zhao; Zhi Zhang; Xueqiang Sun; Mingxin Mu; Tangxin Li; Zhaoyi Guo; et al. (Journal of Invertebrate Pathology, 2025)

Asymmetric C2-functionalization of indoles via visible-light-promoted three-component reaction - Han-Peng Pan; Xiao-Ying Hu; Jun-Hui Luo; Zhao-Jie Fu; Xin-Yi Yao; Meng-Yan Ran; Fang-Xin Wang; Xiang-Zhi Zhang (Molecular Diversity, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

P-CSF: Polar coordinate cloth simulation filtering algorithm for multi-type tunnel point clouds - Zhiyang Zhi; Bingtao Chang; Yuan Li; Zhigang Du; Yipeng Zhao; Xiaodong Cui; Jiahuan Ran; Aiguang Li; Wuming Zhang (Tunnelling and Underground Space Technology, 2025)

EDDS application destabilizes soil organic matter in phytoremediation: Insights from quantity and molecular composition of dissolved organic matter - Yan-ping Zhao; Peng-ran Guo; Zhi-liang Chen; Jin-li Cui; Jian-xu Wang; Chao Chen; Hang Wei; Cheng Wang (Environmental Research, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Seawater corrosive engineering assisted in-situ room temperature synthesis of Ni/Co/Fe trimetallic composition to achieve polyester plastics upgrading and green hydrogen production - Zhao-Hui Zhang; Zhi-Ran Yu; Yi Zhang; Alexandre Barras; Ahmed Addad; Pascal Roussel; Long-Cheng Tang; Sabine Szunerits; Rabah Boukherroub (Chemical Engineering Journal, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Simultaneous determination of twelve natural estrogens in dairy milk using liquid–liquid extraction and solid-phase extraction coupled with gas chromatography-mass spectrometry - De-ming Kong; Zhao Tang; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Yu Liu (Environmental Science and Pollution Research, 2023)

Twelve natural estrogens and ten bisphenol analogues in eight drinking water treatment plants: Analytical method, their occurrence and risk evaluation - Zhao Tang; Ze-hua Liu; Hao Wang; Yi-ping Wan; Zhi Dang; Peng-ran Guo; Yu-mei Song; Sa Chen (Water Research, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Targeting autophagy receptors OPTN and SQSTM1 as a novel therapeutic strategy for osteoporosis complicated with Alzheimer's disease - Ran Duan; Chun-Gu Hong; Meng-Lu Chen; Xin Wang; Zhi-Lin Pang; Hui Xie; Zheng-Zhao Liu (Chemico-Biological Interactions, 2023)

Sustainable utilization of residual grass: effect of anaerobic storage days on chemical composition, fermentation performance, microbial community, and functional profiles of Pennisetum giganteum - Jie Zhao; Zhao-Di Jing; Xue-Jing Yin; Jun-Feng Li; Zhi-Hao Dong; Si-Ran Wang; Tao Shao (Environmental Science and Pollution Research, 2023)

Cobalt chloride exposure disturbs spindle assembly and decreases mouse oocyte development potential - Si-Cheng Zhao; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Hai-Long Wang; Zhi-Ran Xu; Yu Liu (Toxicology, 2023)

Recent advancements in antibiotics containing wastewater treatment by integrated bio-electrochemical-constructed wetland systems (BES-CWs) - Shuang Luo; Zhi-Yuan Zhao; Ying Liu; Ran Liu; Wen-Zong Liu; Xiao-Chi Feng; Ai-Jie Wang; Hong-Cheng Wang (Chemical Engineering Journal, 2023)

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

First report of Bacillus velezensis JK-F2 for the biological control of crown gall in kiwifruit - Ting Ting Chen; Fei Ran; Jin Qiao Shi; Fei Xu Mo; Xian Hui Yin; Zhi Bo Zhao; Zhu Zhu Zhang; Wen Zhi Li; Li Nan He; You Hua Long (Journal of Plant Diseases and Protection, 2022)

Numerical simulation of dynamic responses of semi-rigid rockfall protection barriers subjected to impact loading at different positions - Xin Qi; Lei Zhao; Chao-Ran Hao; Zhi-Xiang Yu; Shi-Chun Zhao (Bulletin of Engineering Geology and the Environment, 2022)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Paenibacillus herberti sp. nov., an endophyte isolated from Herbertus sendtneri - Guan Nan Guo; Xun Zhou; Ran Zhao; Xin Yao Chen; Zhi Ling Chen; Xue Dong Li; Yan Hong Li (Antonie van Leeuwenhoek, 2015)

Chryseobacterium polytrichastri sp. nov., isolated from a moss (Polytrichastrum formosum), and emended description of the genus Chryseobacterium - Xin Yao Chen; Ran Zhao; Zhi Ling Chen; Lei Liu; Xue Dong Li; Yan Hong Li (Antonie van Leeuwenhoek, 2015)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)

Fungal Communities in Decaying Sapwood and Heartwood of a Conifer Keteleeria evelyniana - Han-Bo Zhang; Ming-Xia Yang; Ran Tu; Lei Gao; Zhi-Wei Zhao (Current Microbiology, 2008)